Visual Messages of Conflict Reporting on Twitter: Visual Frames and Ethical Standards - KARADEMIR, Hasan (AUC Knowledge Fountain, 2021)
This comparative study employs the theoretical frameworks of framing and hierarchy of influences model to analyze the ethical forces affecting journalists on Twitter and simultaneously their visual frames constructed in their images on Twitter. It investigates the portrayal of the Yemen conflict in the personal Twitter accounts of Yemeni journalists who were affiliated with the United States (US) and Qatari news organizations. Several studies have pointed out the graphic war coverage of Arab news organizations whereas scholars argue that US news organizations provide sanitized coverage on war zones (Johnson & Fahmy, 2007; Silcock, Schwalbe, & Keith, 2008; Karniel, Lavie-Dinur, & Azran, 2014). This study makes an important contribution to the literature of conflict reporting by adopting a comparative perspective to analyze the Yemeni war-related images of journalists affiliated with different news organizations on social media. Employing a content analysis over a time frame between 2014 and 2019, a total of 1272 Yemen-related tweet images were examined. Results showed differences in the graphic nature and visual narratives of the coverage on Twitter. The findings showed that Yemeni journalists affiliated with US news agencies visually portrayed the Yemen conflict by placing a large focus on the humanitarian consequences of the war. On the other hand, the Yemeni journalists affiliated with Qatari news agencies framed the Yemen conflict from diverse perspectives, including demonstrations and official meetings. Further, results indicated that journalists, who were affiliated with US news agencies, were more likely to share a graphic visual on Twitter than journalists affiliated with Qatari news agencies. Overall, the current study reveals that individual-level influences might be more powerful than organizational-level influences with regard to journalists’ ethics-related decisions of showing graphic visuals on social media platforms.